Thrown Away or Put Away? Window Glass from the Second Half of the 17th Century Deposited in Tykocin Castle, Poland - Magdalena Bis (Fasciculi Archaeologiae Historicae, 2019)
This study is dedicated to window glass discovered in Tykocin castle, deposited in the northern part of the complex, most probably dated to the 1660s. These are remains of windowpanes prepared for the glazing of windows during refurbishment and construction work in the castle building following its destruction in 1656. This paper contains descriptions of those finds including formal, metric and morphological features of the material, structure of the surface and evidence of technical procedures, the character of finds and the reason for the creation of the glass deposit. Finally, the paper discusses the time and circumstances in which the said glass was treated and processed.